Justice, Certainty, and Legal Benefit in the Decision of the Bengkulu Religious High Court on Child Living Expenses after Divorce - Pian, Happy; Beni Ahmad Saebani; Oyo Sunaryo Mukhlas; Tajul Arifin (Faculty of Law, Universitas Pekalongan, 2024)
Due to parental divorce, children become victims and require the husband as the father to pay for the child's living expenses until they are independent. However, the amount of living expenses is not regulated by law and there are no legal sanctions if the father violates the decision. This often harms the mother and child who have custody. This study aims to analyze: (1) Considerations of the Religious Court in determining the child's living expenses after divorce; (2) Implications of the Religious Court Decision regarding the child's living expenses; (3) Legal efforts of the wife against the ex-husband who does not comply with the decision; (4) Clarity and justice of the law in decisions regarding the child's living expenses. The theories used include the theory of legal benefit from Imam Al-Ghazali and the theory of legal principles from Gustav Radbruch. This study is qualitative with a descriptive analysis method, using data from the contents of the Religious Court decision. Data were obtained through observation, interviews, documentation, and content analysis. The results of the study show: (1) Variation in the amount of the child's living expenses; (2) Many violations of the father's actions in fulfilling the cost obligations; (3) Legal efforts taken by the wife; (4) The decision must regulate more property guarantees to facilitate the implementation of the child's living expenses. Legal development is needed regarding clauses in decisions and statutory regulations.